Dependent Group-Oriented Contingencies:A Synoptic Review - Maag, John W. (Journal of Education and Training, 2025)
Dependent group-oriented contingencies (DGOC) are those in which the consequences for a group of students is dependent on the performance of one member or a small subsection of the group. There have been several reviews of group-oriented contingencies but none focusing solely on DGOCs to the exclusion of independent and interdependent types of group-oriented contingencies. Therefore, the purpose of the present review was to describe studies only using DGOCs to determine their feasibility and effectiveness for children and adolescents in school and school-related settings. Results indicated that DGOC can be used effectively, but methods need to be in place to minimize the risk of other students scapegoating and threatening the child for whom the contingency was implemented.